Aged‐care nurses in rural Tasmanian clinical settings more likely to think hypothetical medication error would be reported and disclosed compared to hospital and community nurses. (December 2015) - Carnes, Debra; Kilpatrick, Sue; Iedema, Rick
Abstract: Objective: This study aims to determine the likelihood that rural nurses perceive a hypothetical medication error would be reported in their workplace. Design: This employs cross‐sectional survey using hypothetical error scenario with varying levels of harm. Setting: Clinical settings in rural Tasmania. Participants: Participants were 116 eligible surveys received from registered and enrolled nurses. Main outcome measures: Frequency of responses indicating the likelihood that severe, moderate and near miss (no harm) scenario would 'always' be reported or disclosed. Results: Eighty per cent of nurses viewed a severe error would 'always' be reported, 64.8% a moderate error and 45.7% a near‐miss error. In regards to disclosure, 54.7% felt this was 'always' likely to occur for a severe error, 44.8% for a moderate error and 26.4% for a near miss. Across all levels of severity, aged‐care nurses were more likely than nurses in other settings to view error to 'always' be reported (ranging from 72–96%, P = 0.010 to 0.042, ) and disclosed (68–88%, P = 0.000). Those in a management role were more likely to view error to 'always' be disclosed compared to those in a clinical role (50–77.3%, P = 0.008–0.024). Conclusion: Further research in rural clinical settings is needed to improve the understanding of error management and disclosure.